Piper species: a comprehensive review on their phytochemistry, biological activities and applications - Salehi, Bahare; Zakaria, Zainul Amiruddin; Gyawali, Rabin; Ibrahim, Salam A.; Rajkovic, Jovana; Shinwari, Zabta Khan; Khan, Tariq; Sharifi-Rad, Javad; Ozleyen, Adem; Turkdonmez, Elif; Valussi, Marco; Tumer, Tugba Boyunegmez; et al. (MDPI, 2019)
Piper species are aromatic plants used as spices in the kitchen, but their secondary metabolites have also shown biological effects on human health. These plants are rich in essential oils, which can be found in their fruits, seeds, leaves, branches, roots and stems. Some Piper species have simple chemical profiles, while others, such as Piper nigrum, Piper betle, and Piper auritum, contain very diverse suites of secondary metabolites. In traditional medicine, Piper species have been used worldwide to treat several diseases such as urological problems, skin, liver and stomach ailments, for wound healing, and as antipyretic and anti-inflammatory agents. In addition, Piper species could be used as natural antioxidants and antimicrobial agents in food preservation. The phytochemicals and essential oils of Piper species have shown strong antioxidant activity, in comparison with synthetic antioxidants, and demonstrated antibacterial and antifungal activities against human pathogens. Moreover, Piper species possess therapeutic and preventive potential against several chronic disorders. Among the functional properties of Piper plants/extracts/active components the antiproliferative, anti-inflammatory, and neuropharmacological activities of the extracts and extract-derived bioactive constituents are thought to be key effects for the protection against chronic conditions, based on preclinical in vitro and in vivo studies, besides clinical studies. Habitats and cultivation of Piper species are also covered in this review. In this current work, available literature of chemical constituents of the essential oils Piper plants, their use in traditional medicine, their applications as a food preservative, their antiparasitic activities and other important biological activities are reviewed.